Augmented Reality Application with Real Object Marker of Tanah Lot Temple - Yasa, I Putu Yoga Pertama; Darma Putra, I Ketut Gede; Sri Arsa, Dewa Made (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
Tanah Lot Temple is located in Beraban Village, Kediri District, Tabanan Regency. Tanah Lot Temple is a temple that is included in the Dang Kahyangan Temple. Tanah Lot Temple has buildings scattered in the Tanah Lot Temple Tourism Object. Not all of the buildings in Tanah Lot Temple are known by tourists. Augmented Reality is a visual technology that combines objects or virtual worlds into real-world views in real-time. This study used markerless method and was developed using the Wikitude library and supported by web hosting to store information data and building coordinate data. The system in this study runs dynamically, making it easier to manage data without modifying the program code. Augmented Reality application results with real object marker of Tanah Lot Temple are that it can display information in the form of text narrative and location points along with voice explanations for each building in Tanah Lot Temple.